Maternal fatty acid status during pregnancy versus offspring inflammatory markers: a canonical correlation analysis of the MEFAB cohort - Rouschop, Sven H.; Smolinska, Agnieszka; Gielen, Marij; de Groot, Renate H. M.; Zeegers, Maurice P.; Opperhuizen, Antoon; van Schooten, Frederik J.; Godschalk, Roger W. (Frontiers in Nutrition, 2023)
The development of inflammatory lung disorders in children may be related to maternal fatty acid intake during pregnancy. We therefore examined maternal fatty acid (FA) status during pregnancy and its associations with inflammatory markers and lung conditions in the child by analyzing data from the MEFAB cohort using multivariate canonical correlation analysis (CCA). In the MEFAB cohort, 39 different phospholipid FAs were measured in maternal plasma at 16, 22 and 32 weeks of pregnancy, and at day of birth. Child inflammatory markers and self-reported doctor diagnosis of inflammatory lung disorders were assessed at 7 years of age. Using CCA, we found that maternal FA levels during pregnancy were significantly associated with child inflammatory markers at 7 years of age and that Mead acid (20:3n-9) was the most important FA for this correlation. To further verify the importance of Mead acid, we examined the relation between maternal Mead acid levels at the day of birth with the development of inflammatory lung disorders in children at age 7. After stratification for the child's sex, maternal Mead acid levels at day of birth were significantly related with self-reported doctor diagnosis of asthma and lung infections in boys, and bronchitis and total number of lung disorders in girls. Future studies should investigate whether the importance of Mead acid in the relation between maternal FA status and inflammation and lung disorders in the child is due to its role as biomarker for essential fatty acid deficiency or due to its own biological function as pro-inflammatory mediator.